1999
DOI: 10.1038/sj.bjp.0702486
|View full text |Cite
|
Sign up to set email alerts
|

Pilocarpine modulates the cellular electrical properties of mammalian hearts by activating a cardiac M3 receptor and a K+ current

Abstract: 1 Pilocarpine, a muscarinic acetylcholine receptor (mAChR) agonist, is widely used for treatment of xerostomia and glaucoma. It can also cause many other cellular responses by activating dierent subtypes of mAChRs in dierent tissues. However, the potential role of pilocarpine in modulating cardiac function remained unstudied. 2 We found that pilocarpine produced concentration-dependent (0.1 ± 10 mM) decrease in sinus rhythm and action potential duration, and hyperpolarization of membrane potential in guinea-pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(76 citation statements)
references
References 29 publications
(33 reference statements)
5
70
0
Order By: Relevance
“…Intact M 2 receptor-coupled K þ -channel subunits are essential for cholinergic AF in animal models (Kovoor et al, 2001). In addition to the well-known presence of the M 2 receptor and its corresponding K þ -current (which we will refer to as I KM2 (M 2 receptor-mediated inward rectifier K þ currents)) in mammalian hearts, recent studies indicate the presence in atrial myocytes of various other mAChR subtypes coupled to distinct K þ -currents: I KM3 (M 3 receptor-mediated inward rectifier K þ currents) coupled to the M 3 receptor, typically activated by choline and I KM4 (M 4 receptor-mediated inward rectifier K þ currents) coupled to the M 4 receptor, typically activated by 4-aminopyridine, 4AP (Navarro-Polanco and Sanchez-Chapula, 1997; Shi et al, 1999aShi et al, , b, c, 2003Wang et al, 1999Wang et al, , 2001Wang et al, , 2004. The very rapid atrial firing caused by AF is known to remodel atrial electrical properties in a way that promotes AF occurrence and maintenance (Wijffels et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Intact M 2 receptor-coupled K þ -channel subunits are essential for cholinergic AF in animal models (Kovoor et al, 2001). In addition to the well-known presence of the M 2 receptor and its corresponding K þ -current (which we will refer to as I KM2 (M 2 receptor-mediated inward rectifier K þ currents)) in mammalian hearts, recent studies indicate the presence in atrial myocytes of various other mAChR subtypes coupled to distinct K þ -currents: I KM3 (M 3 receptor-mediated inward rectifier K þ currents) coupled to the M 3 receptor, typically activated by choline and I KM4 (M 4 receptor-mediated inward rectifier K þ currents) coupled to the M 4 receptor, typically activated by 4-aminopyridine, 4AP (Navarro-Polanco and Sanchez-Chapula, 1997; Shi et al, 1999aShi et al, , b, c, 2003Wang et al, 1999Wang et al, , 2001Wang et al, , 2004. The very rapid atrial firing caused by AF is known to remodel atrial electrical properties in a way that promotes AF occurrence and maintenance (Wijffels et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The Journal of Experimental Biology (2014) activity of βγ-and α q -subunits is believed to be involved in the stimulation of the delayed rectifier type K + current, I KM3 (Wang et al, 1999). The molecular basis of the I KM3 current is still unresolved, but it was recently proposed to be carried by the same channels as the I KACh (Navarro-Polanco et al, 2013).…”
Section: Research Articlementioning
confidence: 99%
“…To this end, we have investigated effects of the selective M 3 blocker 4-DAMP (10 −9 mol l )-induced current. The selected agonist concentrations have been shown in a previous patch-clamp study (Wang et al, 1999) to exert subtype-specific effects on muscarinic signaling, while higher concentrations may lead to non-selective binding of the blockers.…”
Section: Effect Of Cch Is Mainly Mediated Via M 2 Muscarinic Receptorsmentioning
confidence: 99%
“…Based on their sensitivity to muscarinic antagonists and to pretreatment with pertussis toxin, it was suggested that the current induced by 4-AP was mediated by M 4 muscarinic receptor (Shi et al, 1999a(Shi et al, , 2003. The current evoked by choline, tetramethylammonium, and the muscarinic agonist pilocarpine (Pilo) was proposed to be mediated by the M 3 muscarinic receptor, and the current was named I KM3 (Shi et al, 1999a(Shi et al, ,b, 2003Wang et al, 1999Wang et al, , 2004. This group postulated that I KM3 modulates cardiac electrical activity (Shi et al, 1999b;Wang et al, 1999) and plays a role in the pathophysiology of atrial fibrillation (Yeh et al, 2007) and cytoprotection against myocardial injuries (Yang et al, 2005).…”
Section: An Outward Rectifier K 1 Current Activated By Muscarinic Ligmentioning
confidence: 99%
“…The current evoked by choline, tetramethylammonium, and the muscarinic agonist pilocarpine (Pilo) was proposed to be mediated by the M 3 muscarinic receptor, and the current was named I KM3 (Shi et al, 1999a(Shi et al, ,b, 2003Wang et al, 1999Wang et al, , 2004. This group postulated that I KM3 modulates cardiac electrical activity (Shi et al, 1999b;Wang et al, 1999) and plays a role in the pathophysiology of atrial fibrillation (Yeh et al, 2007) and cytoprotection against myocardial injuries (Yang et al, 2005). Despite the prediction of a novel channel, the molecular correlates of the K 1 channel subunits that underlie I KM3 remained elusive (Yang and Nerbonne, 2016).…”
Section: An Outward Rectifier K 1 Current Activated By Muscarinic Ligmentioning
confidence: 99%